Schinus Terebinthifolius raddi: estudo farmacognóstico e investigação da atividade biológica de extratos e frações - Salvi Júnior, Ademir [UNESP] (2013)
The use of medicinal plants has reached a increasing public since the return to natural medicine. It is a worrisome the indiscriminate use of medicinal plants without proper pharmacognostic knowledge. Schinus terebinthifolius Raddi, known as mastic-red, is a native tree species, occurring in the Atlantic Forest, Riparian Forest and Cerrado. Their pharmacological properties have attracted the interest of research groups, since their inclusion in the Brazilian Pharmacopoeia (1929) and recently attached as species of concern in the RENISUS (2009) and RENAME (2012). Despite their pharmacological potential, the designation of pharmacogeno, as the shells of the trunk, part of the plant depends on a regeneration process after withdrawal, according to the demand can be viewed as an environmental risk to the species, This study seeks recognition of laboratory sheets of the species as a drug, aiming their conservation and rational use.This work aimed to study the pharmacognostic aspects of leaves of S. terebinthifolius Raddi, of the three localities, to contribute with information relating to quality control physicochemical vegetal drug, as well as evaluate the antimicrobial and antiproliferative activity in vitro of extracts, essential oil and fractions obtained from leaves of S. terebinthifolius. The analyses of quality control were performed according to pharmacopoeical and non pharmacopoeical standards, the antimicrobial activity according to standards of the CLSI for microdilution plate and bioautography, and antiproliferative activity by the test of sulforhodamine B. The results of physicochemical characterization presented as mean values, solid residue 40.32%, water loss on drying 59.68%, grain size between coarse and moderately coarse powder, average particle size of 0.3102 mm, density 0.57 g /mL, moisture content of 7.54%, pH 4.12 U, total ash 5.94%, acid insoluble ash 0.36% and extractives content 29.79%; the phytochemical analysis ...